Production of Food and Feed Additives From Non-food-competing Feedstocks: Valorizing N-acetylmuramic Acid for Amino Acid and Carotenoid Fermentation With Corynebacterium glutamicum - Sgobba, Elvira; Blöbaum, Luisa; Wendisch, Volker F. (Frontiers in Microbiology, 2018)
Corynebacterium glutamicum is used for the million-ton-scale production of food and feed amino acids such as L-glutamate and L-lysine and has been engineered for production of carotenoids such as lycopene. These fermentation processes are based on sugars present in molasses and starch hydrolysates. Due to competing uses of starch and sugars in human nutrition, this bacterium has been engineered for utilization of alternative feedstocks, for example, pentose sugars present in lignocellulosic and hexosamines such as glucosamine and N-acetyl-D-glucosamine (GlcNAc). This study describes strain engineering and fermentation using N-acetyl-D-muramic acid (MurNAc) as non-food-competing feedstock. To this end, the genes encoding the MurNAc-specific PTS subunits MurP and Crr and the etherase MurQ from E. coli K-12 were expressed in C. glutamicum ΔnanR. While MurP and MurQ were required to allow growth of C. glutamicum ΔnanR with MurNAc, heterologous Crr was not, but it increased the growth rate in MurNAc minimal medium from 0.15 h-1 to 0.20 h1. When in addition to murP-murQ-crr the GlcNAc-specific PTS gene nagE from C. glycinophilum was expressed in C. glutamicum ΔnanR, the resulting strain could utilize blends of GlcNAc and MurNAc. Fermentative production of the amino acids L-glutamate and L-lysine, the carotenoid lycopene, and the L-lysine derived chemicals 1,5-diaminopentane and L-pipecolic acid either from MurNAc alone or from MurNAc-GlcNAc blends was shown. MurNAc and GlcNAc are the major components of the bacterial cell wall and bacterial biomass is an underutilized side product of large-scale bacterial production of organic acids, amino acids or enzymes. The proof-of-concept for valorization of MurNAc reached here has potential for biorefinery applications to convert non-food-competing feedstocks or side-streams to valuable products such as food and feed additives.